Work adjustment of practitioner-turn-academics at Malaysian research universities - Shamsir, Rouzil Armiza; Ismail, Maimunah (University Publications, 2013)
At present the academia is looking at experienced practitioners as the new academics. Some have experience working in industries while others shifted to the public IHLs for their second career. They are known as Practitioners-Turned-Academics (PTAs). These newcomers need personal and work adjustment during the transition years. This article explores the relationship between the individualrelated factors, job-related factors and organizational-related factors, and work adjustment of the PTAs. The need to study their work adjustment stems from the fact that academia itself is experiencing changes in terms of vision and mission one of which is becoming a research university. Based on the Theory of Work Adjustment (TWA), this article reports the findings of the study.